PARADIGMATIC OF SYNTAXEMES EXPRESSING TEMPORALITY - Dilmurodova Madina (Journal of new century innovations, 2023)
Abstract: The present article is devoted to an actual theme of modern grammar-syntactic paradigmatic of syntaxemes, expressing temporality in modern English and Uzbek languages in comparative aspect.